Um estudo funcionalista sobre a hipotaxe adverbial casual e a hipotaxe adverbial conformativa em textos oficiais do Paraná, produzidos entre os séculos XVIII a XX - Gonçalves, Bianca de Almeida (2011)
The present study investigated the roles of cause and conformity by the connector as in official letters written between the eighteenth, nineteenth and twentieth centuries, as found in reports issued official letters to the State Government between the XVIII and XIX, for messages sent by the Governor of the State Legislature to Congress Paraná between the nineteenth and twentieth centuries and reports submitted to the Governor in the nineteenth and twentieth centuries. The corpora used in this study were drawn from two sources: letters, from the research project for the History of Portuguese Paranaense: diachronic studies in manuscripts of the seventeenth century, developed by the Department of Literature and Classical Vernacular, of Universidade Estadual de Londrina, and the reports and messages, the Public Archives of Paraná. The corpora were analyzed from the perspective of Systemic Functional Grammar, Halliday's (1985), aiming to understand the behavior manifest syntactic-semantic constructions by Oracion question and as spearheaded by the item like in order to identify its position in the clausal structure, the function to which provide their uses and subtypes of relations that express (real epistemic or between speech acts, as Sweetser (1990). The results show that the causative construction, as well as those complying, are undergoing a process of grammaticalization in that the relations established between the domains of content are more frequent, and that the causal reading is losing space for compliance when in postposition. With respect to the difference between the genres analyzed, we found a relationship between linguistic structures and power relations instituted amongst listeners. This relationship is manifested by the types of hypotaxis, type of reaction expressed by prayer hypotactic as Sweetser (1990), their position in prayer, and sharing the identity of the subject of the prayers and the time involved mode, and semantics of the verbs used in prayers hypotactic.